2020
DOI: 10.1111/opo.12725
|View full text |Cite
|
Sign up to set email alerts
|

Optical and imaging properties of a novel multi‐segment spectacle lens designed to slow myopia progression

Abstract: Purpose High sampling density optical metrology combined with pupil‐ and image‐plane numerical analyses were applied to evaluate a novel spectacle lens containing multiple small zones designed to slow myopia progression. Methods High‐resolution aberrometry (ClearWave, http://www.lumetrics.com) was used to sample wavefront slopes of a novel spectacle lens, Defocus Incorporated Multiple Segments (DIMS) (http://www.hoya.com), incorporating many small, positive‐powered lenslets in its periphery. Using wavefront sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 32 publications
(40 reference statements)
3
55
0
4
Order By: Relevance
“…The results of VA tested using FrACT in the current study were consistent with the findings of CS. Jaskulski et al also found that the DIMS decreased contrast sensitivity at high spatial frequencies ( Jaskulski et al, 2020 ). For VA in high luminance and high contrast, HC induced the most vision loss by approximately 0.09 logMAR, followed by HAL and SAL.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The results of VA tested using FrACT in the current study were consistent with the findings of CS. Jaskulski et al also found that the DIMS decreased contrast sensitivity at high spatial frequencies ( Jaskulski et al, 2020 ). For VA in high luminance and high contrast, HC induced the most vision loss by approximately 0.09 logMAR, followed by HAL and SAL.…”
Section: Discussionmentioning
confidence: 97%
“…Other than the configuration of lenslets, which resulted in less fragmented optics due to small aperture, the diameter of lenslets was also a factor impacting optical performance. HAL and SAL had a slightly larger lenslet diameter than HC (1.03 vs. 1.12 mm), which reduced diffraction caused by fragmented optics due to smaller aperture ( Jaskulski et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with that of another separate study in which better high contrast visual acuity in children was also found for HAL and SAL than the DIMS lens 38 . Another recent investigation combined high sampling density optical metrology with pupil‐ and image‐plane numerical analyses to evaluate the same lens 40 . Both visual inspection and wavefront metrology revealed that the lenslets gave a coverage factor of approximately 40%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, emmetropization might not only be caused by increased photoreceptor sensitivity but also due to focusing short-wavelength light in front of the retina based on longitudinal chromatic aberration and induced monochromatic myopic defocus [36]. A myopic defocus appears protective against myopia progression in human and animal studies [21,34,37,47,[72][73][74][75]. The complexity around short-wavelength retinal light stimulation or stimulation with other wavelengths and myopia is high.…”
Section: Influence Of Different Wavelength Ranges In Context Of Myopia Controlmentioning
confidence: 99%